Methods for searching and using maps using internet resources in geography lessons. (Journal of Universal Science Research, 2023)
This article explores the integration of internet resources in geography lessons, specifically focusing on methods for searching and using maps. With the advent of technology, educators have a plethora of online tools and resources at their disposal to enhance geographical learning experiences. The article delves into the literature, presents various methods, reports on results, and discusses implications for geography education.